Reactive Neuroblastosis in Huntington’s Disease: A Putative Therapeutic Target for Striatal Regeneration in the Adult Brain - Kandasamy, Mahesh; Aigner, Ludwig (Frontiers in Cellular Neuroscience, 2018)
The cellular and molecular mechanisms underlying the reciprocal relationship between adult neurogenesis, cognitive and motor functions have been an important focus of investigation in the establishment of effective neural replacement therapies for neurodegenerative disorders. While neuronal loss, reactive gliosis and defects in the self-repair capacity have extensively been characterized in neurodegenerative disorders, the transient excess production of neuroblasts detected in the adult striatum of animal models of Huntington’s disease (HD) and in post-mortem brain of HD patients, has only marginally been addressed. This abnormal cellular response in the striatum appears to originate from the selective proliferation and ectopic migration of neuroblasts derived from the SVZ. Based on and in line with the term “reactive astrogliosis”, we propose to name the observed cellular event “reactive neuroblastosis”. Although, the functional relevance of reactive neuroblastosis is unknown, we speculate that this process may provide support for the tissue regeneration in compensating the structural and physiological functions of the striatum in lieu of ageing or of the neurodegenerative process. Thus, in this review, we comprehend different possibilities for the regulation of striatal neurogenesis, neuroblastosis and their functional relevance in the context of HD.